Artificial Intelligence–Driven Innovations in Forensic Odontology for Human Identification: A Narrative Review - Pasaribu, Roben S.; Muliawati, Dian; Yunus, Aditia D. (Universitas Sam Ratulangi, 2026)
Abstract: Forensic odontology is a branch of forensic science that plays a role in identification, including age and sex estimation. The identification results acted as valid evidence based on the science of forensic dentistry, which is used in the judicial process. Traditional methods of identification have the disadvantage of subjectivity on the part of the examiner. The analysis results can be biased, leading to incorrect conclusions. The rapid development of technology has impacted the field of forensic odontology. This review aimed to evaluate the potential and applications of AI in forensic odontology. Artificial intelligence (AI) is a computer-based system designed using principles of human intelligence. The application of artificial intelligence to assist forensic experts is growing and being explored increasingly. Artificial intelligence in forensic odontology plays a role in gender determination, age estimation, lip print analysis, toothmark analysis, personal identification, and facial reconstruction. The AI-based identification process is expected to eliminate the researcher's subjectivity and improve the accuracy of the results. In conclusion, artificial intelligence (AI) has significantly influenced forensic odontology by supporting key forensic tasks, including age estimation, sex determination, cheiloscopy analysis, and facial reconstruction. Keywords: forensic odontology; artificial intelligence; identification process; application